Urban Regions Shifting to Circular Economy: Understanding Challenges for New Ways of Governance - Obersteg, Andreas (2019)
Urban areas account for around 50% of global solid waste generation. In the last decade, the European Union has supported numerous initiatives aiming at reducing waste generation by promoting shifts towards Circular Economy (CE) approaches. Governing this process has become imperative. This article focuses on the results of a governance analysis of six urban regions in Europe involved in the Horizon 2020 project REPAiR. By means of semi-structured interviews, document analysis and workshops with local stakeholders, for each urban area a list of governance challenges which hinder the necessary shift to circularity was drafted. In order to compare the six cases, the various challenges have been categorized using the PESTEL-O method. Results highlight a significant variation in policy contexts and the need for these to evolve by adapting stakeholders’ and policy-makers’ engagement and diffusing knowledge on CE. Common challenges among the six regions include a lack of an integrated guiding framework (both political and legal), limited awareness among citizens, and technological barriers. All these elements call for a multi-faceted governance approach able to embrace the complexity of the process and comprehensively address the various challenges to completing the shift towards circularity in cities.